2010
DOI: 10.2337/dc10-1371
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Episodes of Hypoglycemia as a Potential Aggravating Factor for Preclinical Atherosclerosis in Subjects With Type 1 Diabetes

Abstract: OBJECTIVETo evaluate through early preclinical atherosclerosis assessment whether repeated episodes of hypoglycemia represent an aggravating factor for macrovascular disease in type 1 diabetes.RESEARCH DESIGN AND METHODSAfter sample-size calculation, a case-control study of 25 patients with type 1 diabetes and repeated severe/nonsevere hypoglycemia (H-group) compared with 20 age- and sex-matched type 1 diabetes control subjects (C-group) was designed. Assessment of preclinical atherosclerosis consisted of flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 25 publications
6
79
1
2
Order By: Relevance
“…Our findings are supported by two previous studies that investigated atherosclerosis risk in T1DM (13,14). The DCCT/EDIC project reported that the prevalence of coronary artery calcification, an established atherosclerosis marker, was linearly correlated with the incidence rate of hypoglycemia on the DCCT stage (14).…”
Section: Comparison With Previous Studiessupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings are supported by two previous studies that investigated atherosclerosis risk in T1DM (13,14). The DCCT/EDIC project reported that the prevalence of coronary artery calcification, an established atherosclerosis marker, was linearly correlated with the incidence rate of hypoglycemia on the DCCT stage (14).…”
Section: Comparison With Previous Studiessupporting
confidence: 80%
“…The Action to Control Cardiovascular Risk in Diabetes (ACCORD) study of T2DM found a weakly inverse association between the annualized number of hypoglycemic episodes and the risk of death (11,12). By contrast, some studies find that repeated hypoglycemia may be an aggravating factor to atherosclerosis in T1DM (13,14). Studies on the compromised sympatheticadrenal reaction in patients with repeated hypoglycemia have been inconclusive regarding whether such a reaction may further damage intravascular coagulation and thrombosis (15) or decrease the vulnerability of these patients to adverse health outcomes (12).…”
mentioning
confidence: 99%
“…Our patients did not show a particular metabolic instability, and hypoglycemia was not severe or very frequent. However, metabolic instability may also worsen c-IMT, and for this reason, another study performed in Spain with such patients presented a higher c-IMT compared with our cohort (27).…”
Section: Discussionmentioning
confidence: 90%
“…From the perspective of acute cardiovascular events, the net effect of tight glycemic control with insulin in diabetes in ORIGIN was harm. However, it is conceivable that ORIGIN was too short to demonstrate an effect of glycemic control to significantly interrupt the pathogenesis of atherosclerotic macrovascular disease (23). It remains to be seen if early and sustained glycemic control does so.…”
Section: Upside Of Glycemic Control: Reduced Microvascular Complicationsmentioning
confidence: 99%